2021
DOI: 10.1155/2021/5514525
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Urena lobata Fibre Treatment on Mechanical Performance Development in Hybrid Urena lobata: Fibre/Gypsum Plaster Composites

Abstract: Autogenous shrinkage is related to the chemistry and changes in the internal structure of the cement concrete paste on drying. This problem of drying shrinkage in early stages that occur without any moisture transfer to the surrounding environment has triggered the incorporation of fibres in the cement concrete matrix to fill the micropores and control cracking (autogenous shrinkage). This study aimed at investigating the potential use of Urena lobata (UL) fibre as microreinforcement in enhancing mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…3) The compressive strengths obtained for the palm kernel shell and spikelet fibre composites at 28 days curing ranged from 12.26Mpa to 25.34 Mpa, which met the compressive strength requirements with reference to previous research findings that the compressive strength of palm kernel shell composites ranges from 5 to 25 Mpa based on mix design. Kengoh et al (2021) The research also revealed that the physical and mechanical properties of palm kernel shell and spikelet fibers aggregate are satisfactory for the production of structural composites. Ezeudu et al…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…3) The compressive strengths obtained for the palm kernel shell and spikelet fibre composites at 28 days curing ranged from 12.26Mpa to 25.34 Mpa, which met the compressive strength requirements with reference to previous research findings that the compressive strength of palm kernel shell composites ranges from 5 to 25 Mpa based on mix design. Kengoh et al (2021) The research also revealed that the physical and mechanical properties of palm kernel shell and spikelet fibers aggregate are satisfactory for the production of structural composites. Ezeudu et al…”
Section: Discussionmentioning
confidence: 94%
“…The specimen dimension was taken before the testing. ACI (2003), Kengoh et al (2021) The testing was carried out for 7 days, and 28 days specimen after curing…”
Section: Compression Characterization Of Samples For 7 and 28 Daysmentioning
confidence: 99%
“…Demineralised water was then added and the three components were mixed for approximately 6 min. 28 The fibrous paste was then immediately poured into a 160 mm × 40 mm × 12 mm silicone mould and lightly stirred to distribute the mixture evenly. After 15 min of drying, the samples were removed from the mould and left in the open air (temperature 25 ± 2°C and relative humidity 55%) until the mass stabilised (total drying time equal to 6 days).…”
Section: Methodsmentioning
confidence: 99%
“…Ebanda and Atangana 27 conducted research on the thermal conductivity and diffusivity of hardened gypsum, woven, unidirectional and random reinforcement of Rheckthophyllum camerunense tropical fibre bundles as a potential substitute for sisal and glass fibres. Kengoh et al 28 showed that Urena lobata fibre bundles can be used to improve the flexural strength of plaster. Betené 29 showed that fibre bundles of Rheckthophyllum camerunense and Ananas comosus can be added to plaster to improve its toughness and flexural strength, and to limit its cracking on indentation.…”
Section: Introductionmentioning
confidence: 99%
“…It has low tensile strength and brittleness, as well as being low cost, easy shaping and lightness make gypsum favorable. Plasterboard walls and ceilings are widely used in buildings due to their many superior properties [1][2][3]. However, the use of such internal structural elements is limited in cases of damage, fire and insulation.…”
Section: Introductionmentioning
confidence: 99%